2022
DOI: 10.3390/ijerph19063247
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Removal of Malachite Green Using Calcium-Functionalized Magnetic Biochar

Abstract: To efficiently remove malachite green (MG), a novel calcium-functionalized magnetic biochar (Ca/MBC) was fabricated via a two-step pyrolysis method. Iron-containing oxides endowed the target complexes with magnetic properties, especially the chemotactic binding ability with MG, and the addition of calcium significantly changed the morphology of the material and improved its adsorption performance, especially the chemotactic binding ability with MG, which could be confirmed through FTIR, XPS, and adsorption exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 42 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The N 2 adsorption-desorption isotherms of SSB displayed a type IV curve (Figure 1). The absence of the H3-type hysteresis loop isotherm is due to the irregular structure of SSB, as illustrated with SEM [38]. Figures 2 and 3 show the SEM images of the raw material and SSB at different magnifications.…”
Section: Adsorbent Preparation and Characterizationmentioning
confidence: 82%
See 2 more Smart Citations
“…The N 2 adsorption-desorption isotherms of SSB displayed a type IV curve (Figure 1). The absence of the H3-type hysteresis loop isotherm is due to the irregular structure of SSB, as illustrated with SEM [38]. Figures 2 and 3 show the SEM images of the raw material and SSB at different magnifications.…”
Section: Adsorbent Preparation and Characterizationmentioning
confidence: 82%
“…Sustainability 2022, 14, x FOR PEER REVIEW 5 of 16 SSB, as illustrated with SEM [38]. Figures 2 and 3 show the SEM images of the raw material and SSB at different magnifications.…”
Section: Adsorbent Preparation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Estevan D. Cruz [22] fixed Ca/double hydroxide on biochar by co-precipitation method, and the material had a good adsorption effect on congo red. Pengjie W. [23] reported that calcium doping can significantly change the morphology of the adsorbent material and improve the adsorption performance. In particular, the synthesized calcium-based magnetic biochar can efficiently adsorb malachite green dye.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a variety of adsorbents such as graphene oxide [12], biochar [13], metal organic framework materials (MOFs) [14], porous carbon [15] and their derivatives have been used for removal of MG. Among these materials, MOFs are a type of metal ion-polydentate organic ligand complexes nanomaterials, which are widely used in gas storage [16], adsorption [17], catalysis [18] and sensing [19] and other elds due to their rich metal active sites, large surface area and orderly pore structure.…”
Section: Introductionmentioning
confidence: 99%